2007
DOI: 10.1021/jp075346b
|View full text |Cite
|
Sign up to set email alerts
|

How Anesthetics, Neurotransmitters, and Antibiotics Influence the Relaxation Processes in Lipid Membranes

Abstract: We used pressure perturbation calorimetry to investigate the relaxation time scale after a jump into the melting transition regime of artificial lipid membranes. This time is equivalent to the characteristic rate of domain growth. The studies were performed on single-component large unilamellar and multilamellar vesicle systems with and without the addition of small molecules such as general anesthetics, neurotransmitters, and antibiotics. These drugs interact with membranes and affect melting points and profi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 79 publications
4
61
0
Order By: Relevance
“…The fluctuation-dissipation theorem implies that large fluctuations go along with longer fluctuation lifetimes. This results in longer mean open-lifetimes of lipid pores in the transition range (34,35). The lifetimes of lipid membrane-fluctuations span the range from milliseconds to seconds, and are therefore just in the range observed for protein channel open-lifetimes.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The fluctuation-dissipation theorem implies that large fluctuations go along with longer fluctuation lifetimes. This results in longer mean open-lifetimes of lipid pores in the transition range (34,35). The lifetimes of lipid membrane-fluctuations span the range from milliseconds to seconds, and are therefore just in the range observed for protein channel open-lifetimes.…”
Section: Introductionmentioning
confidence: 91%
“…Various authors have shown that transitions are influenced by drugs, e.g., by anesthetics, neurotransmitters or peptides (35). Anesthetics lower the transition temperature of lipids by a well-known mechanism called melting-point depression (3,(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…5HT acts as a neurotransmitter in the central nervous system of animals. The interaction between 5HT and phospholipid membranes has become of interest in recent years, and has been studied by calorimetry [1][2][3], fluorometry [4], and theoretical calculations [5,6]. The researchers in this field are requiring a reliable value of the hydrophobicity of the cationic form of 5HT, because 5HT is protonated at physiological pH.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of a T m temperature reduction and a decrease in the transition width is an unusual one. Most commonly, with the introduction of compounds that decrease the T m (such as anesthetics and cholesterol) the transition peaks also broaden, as would be expected with the introduction of impurities [36][37][38]. Furthermore, with most lipid mixtures, the transition peak broadens rather than sharpens [18,22,25,26].…”
Section: Effect Of Nucleation Sites Lipid Packing and Interfacial Rmentioning
confidence: 97%